2006
DOI: 10.1016/j.pain.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex stimulation for long-term relief of chronic neuropathic pain: A 10 year experience

Abstract: Chronic subthreshold stimulation of the contralateral precentral gyrus is used in patients with intractable neuropathic pain for more than 15 years. The aim of this study was to analyse retrospectively our own patient group with long term follow-up of 10 years. Seventeen patients with chronic neuropathic pain were treated with contralateral epidural stimulation electrodes. In 10 cases, trigeminal neuropathic pain (TNP) and in seven cases post-stroke pain (PSP) were diagnosed. The placement of the electrodes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(123 citation statements)
references
References 41 publications
3
114
0
6
Order By: Relevance
“…Several kinds of navigation systems for neurosurgical assistance can be used to estimate the position of the central sulcus from skin surface (Tirakotai et al, 2007). Neuronavigation combined with fMRI data help to decide the best position for craniotomy and for placement of the stimulating paddle (Rasche et al, 2006). A drawback of neuronavigation is the requirement that the patient's head be fixed in a 3-point pin holder or vacuum headrest (Tirakotai et al, 2007), which several patients may not tolerate under local anesthesia.…”
Section: Neuronavigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several kinds of navigation systems for neurosurgical assistance can be used to estimate the position of the central sulcus from skin surface (Tirakotai et al, 2007). Neuronavigation combined with fMRI data help to decide the best position for craniotomy and for placement of the stimulating paddle (Rasche et al, 2006). A drawback of neuronavigation is the requirement that the patient's head be fixed in a 3-point pin holder or vacuum headrest (Tirakotai et al, 2007), which several patients may not tolerate under local anesthesia.…”
Section: Neuronavigationmentioning
confidence: 99%
“…Some surgeons place the electrode perpendicular to the central sulcus above the precentral (cathode) and postcentral (anode) gyri for the supposed improved selectivity (Nguyen et al, 1999), others in a parallel fashion, i.e. with all contacts on the M1 or S1 Rasche et al, 2006). Moreover, no polarity-related difference in pain relief is seen for most patients with epidural electrodes (Katayama et al, 1998).…”
Section: Electrode Implantationmentioning
confidence: 99%
“…10,11 Finally, in 1998, Nguyen et al 12 first reported using stimulation of this same region to treat PD, completing the overlap of treatment by using MCS to treat both chronic pain and movement disorders. For the period between 1991 and 2007, a Medline review revealed 512 cases of treatment with MCS, for either pain (422 cases 10,13-52 ), stroke rehabilitation (9 cases 13,49,53 ), or movement disorders (84 cases, 22 of them being mixed MCS and deep brain stimulation [DBS]). 12,26,54 -64 Some of the studies may have included previously reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…Tricyclic antidepressants, gabapentin, intrathecally local anaesthetics and corticosteroids are the medical treatments used. In the surgical approach, peripheral neurectomy, percutaneous gangliolysis, motor cortex stimulation, stereotactic trigeminal nucleotomy, stimulation of the Gasserian ganglion and trigeminal rootlets are used for trigeminal neuropathic pain (3,12,13,16,18,20,21,26,27). However, we performed CT-guided trigeminal tractotomy for the treatment of this special case.…”
Section: Discussionmentioning
confidence: 99%